Online Shopping Behavior during COVID-19 Pandemic – Generation Z Perspective - Stefan-Alexandru CATANA; Cristina Petronela SIMION; Mirona Ana Maria POPESCU; Andreea BARBU (Communications of International Proceedings, 2021)
The impact of the COVID-19 pandemic has been remarkable in all aspects of life from economic to social interaction. This paper follows another research conducted by the authors on the main factors that influence online shopping behavior. The data were gathered through quantitative and qualitative research methods, such as interviews and surveys. The paper indicates that generation Z consumers tend to use payment on delivery, online payment using debit and credit cards, and gift cards or vouchers. Moreover, the principal device used for online shopping is represented by mobile phone followed by the computer.
Keywords: Generation Z; Online shopping behavior; COVID-19 pandemic.